High light availability offsets low naturalness regarding diversity but cannot compensate for reduced ecological value: A case study of near-natural forests and tree plantations in Serbia - Khanh Vu Ho; Mirjana Ćuk; Andraž Čarni; Dragana Vukov; Miloš Ilić; László Erdös (Journal of Forest Science)
In Eastern Europe, near-natural forest patches are decreasing and are gradually replaced by non-native plantations. Tree plantations are commonly thought to be simple ecosystems with low conservation value, although this conclusion is mainly based on simple taxonomic diversity indices, which ignore functional and phylogenetic diversity. In this study, our objective was to compare species composition, diagnostic species, taxonomic, functional, and phylogenetic diversity, as well as naturalness status between two near-natural forest types (Quercus-Tilia and Populus alba) and two common plantation types (non-native Pinus sylvestris and non-native Robinia pseudoacacia) in the Deliblato Sands, Serbia. Our results showed that the species composition significantly differed in the four habitats. Each habitat had some species that were significantly concentrated in them. Most of the diagnostic species in the Quercus-Tilia forests were forest specialist plant species, while those in Populus alba forests were species associated with warmer and drier habitats, whereas the plantations hosted diagnostic species with broader ecological tolerances. Native species richness, total species diversity, and functional and phylogenetic diversity were similar in the four studied habitats, which can be explained by the combined effects of light regime and naturalness. We assessed low naturalness (i.e. high degradation) in plantations, which can be expected to reduce diversity. However, higher light availability was probably able to compensate for this effect. Non-native plantations, especially Robinia pseudoacacia plantations, were the most degraded and hosted the highest non-native species richness, implying that they are ecologically undesirable. In light of our results, we suggest that near-natural forest stands should be protected and efforts to restore these forests should be given high priority. Furthermore, it is advisable to continue with a forestry strategy that involves replacing non-native plantations with native ones, such as Tilia tomentosa, in the Deliblato Sands.